Is Michel Henry's Radical Phenomenology of Life a Christian Philosophy? - Hao, Changchi (Religions, 2022)
This paper examines two fundamental claims by Michel Henry on his philosophy’s relationship with classical phenomenology (Husserl and Heidegger) and Christianity. It shows in what way Henry’s phenomenology is the radicalization and absolutization of classical phenomenology: pure phenomenological truth is the identification of appearing and what appears rather than the separation of the two. According to Henry, his notions of life and truth is fully in accordance with Christianity’s Revelation of God. In the last part, the paper challenges Henry’s claim that his phenomenology is a Christian philosophy from a Kierkegaardian point of view and argues that Henry’s phenomenology is, as a matter of fact, a philosophy without Christ. Contrary to a popular viewpoint that Michel Henry is a Christian thinker of our age, I would argue that Henry’s concept of God and Christ is essentially a scholarly philosophical invention. If Henry’s philosophy is an absolute and ultimate form of phenomenology, then it is reasonable to draw a conclusion that Christ as the Truth of Christianity is outside the boundary of phenomenology.